Lead poisoning and its effects on bone density - Alireza Zabihi; Omid Mehrpour; Samaneh Nakhaee; Elham Atabati (Scientific Reports)
Abstract Lead poisoning is a significant health concern, impacting multiple organs in the body, including the musculoskeletal system. While some studies suggest a link between lead exposure and reduced Bone Mineral Density (BMD), others report no significant relationship. This study aims to address this research gap by comparing the prevalence of osteoporosis and BMD in patients with lead poisoning to that of healthy individuals. In this study, 35 lead poisoning patients admitted to the poisoning departments of Valiasr Hospital in Birjand and Imam Reza Hospital in Mashhad were compared with 35 age- and gender-matched healthy controls. The healthy group had Blood Lead concentrations (BLC), < 10 µg/dl and did not use drugs. Blood samples were collected to measure lead concentrations, and osteoporosis was compared between the two groups. Osteoporosis was diagnosed using a DEXA (Dual-energy X-ray absorptiometry) machine made in Spain. Data were entered into SPSS software version 22 and analyzed at a significance level of 5%. The mean BLC in the lead poisoning group was significantly higher than the healthy group (P < 0.05). However, there was no significant difference in the frequency distribution of osteoporosis between the groups (P > 0.05). The mean Z and T scores of femur in both groups showed no significant difference (P > 0.05). In contrast, the mean T and Z scores of L1, L2, L3, and L4 lumbar bones in the lead poisoning group were significantly lower than those in the healthy group (P < 0.05). The results of this study suggest that the prevalence of osteoporosis in people with lead poisoning is not different from that in healthy individuals. Nonetheless, bone density indices of lumbar vertebrae were affected in lead-poisoned individuals.